Rationalization of drug use with DAGUSIBU: Strengthening understanding for TP-PKK - Sabtanti Harimurti; Andy Eko Wibowo; Pinasti Utami; Nurul Maziyyah; Zelmi Dwi Novita; Astri Fatmah; Tyas Fabandari Dewi Hapsari; Andi Regita Pasha (Community Empowerment, 2022)
GeMa CerMat is a movement launched in 2016, which is expected to achieve rational treatment in the wider community. To support this movement, the Indonesian Pharmacists Association launched DAGUSIBU (DA = dapatkan (Get), GU = gunakan (Use), SI = simpan (Store), and BU = buang (Dispose) of medicine) to educate the entire community to understand how to get good medicine, how to use medicine properly, how to store medicine properly and how to dispose of medicine properly. Based on observations to the head of Gampeng Pajangan Bantul hamlet, the community does not understand how to take medicine rationally for their relatives who take regular medicine and also do not understand how to manage the huge amount of medicine they get every month. Based on this evidence, the DAGUSIBU training was conducted to strengthen the understanding of rational drug use for the TP-PKK (Family Welfare Development Team) Gampeng hamlet, Triwidadi village, Pajangan Bantul. The TP-PKK in the hamlet consists of 25 health cadres and woman society village. At the end of the training session, the practice of destroying drugs was carried out. The results of the training showed a significant increase in understanding on DAGUSIBU after training. Evaluation was taken by giving pre-test and post-test according to DAGUSIBU. The DAGUSIBU guide book for Health cadres and the general public is given to TP-PKK at the end of the activity to help the community understand of DAGUSIBU and become a source of information on drug use.